HYPOCHOLESTEROLEMIA SECONDARY TO ATROVASTATIN THERAPY - Ali, Shafqut; Khan, Shahbaz Ali; Iram, Samia (Journal of Ayub Medical College Abbottabad, 2010)
After the advent of Statins in 1960’s, they are being extensively used as Antiathrogenic drug for Primary Hyperlipidemia, Angina, Ischemic Heart Disease (Medical or Post Surgical), Atherosclerosis, Diabetes mellitus and Hypertension. Rarely, these drugs have been observed to cause hypocholesterolemia. We present a case of forty years old male who was started on Atorvastatin after his angioplasty following anterior myocardial infarction. Six weeks after the start of antilipid drug patient developed symptoms of phobias, nightmares, insomnia, forgetfulness, body aches, muscle cramps, cognitive, sexual and psychomotor disturbances. On investigation he was found to have hypocholesterolemia. Atorvastatin was stopped and dietary restrictrictions were lifted. Over five month patients symptoms resolved as the serum cholesterol levels became normal. Because of similarities of symptoms of hypocholesterolemia secondary to antilipid therapy and the disease itself, hypocholesterolemia was overlooked initially by physicians. Patients on antilipids must be evaluated for any fall in serum cholerterol if they develop unusual symptoms and patients on long term antilipids must have regularly lipid profile checked. Keywords: Hypocholesterolemia, Statins, Fiberates, HMG-CoA reductase, VLDL, HDL, Triglycerides, LPL